Design and development of multifunctional Raman active noble metals nanoprobes for the detection of malaria and tuberculosis biomarkers - Mlambo, Mbuso (My University, 2016)
Surface enhanced Raman spectroscopy (SERS) has emerged as a surface sensitive vibrational technique that leads to the enhancement of the Raman scattering molecules on or close to the surface of a plasmonic nanostructure. The enhancement is found to be in orders of 104 to 1015, which allows the technique to be sensitive enough to detect a single molecule. In this study, we report on the synthesis of different sizes of gold and silver nanoparticles (AuNPs and AgNPs) and gold nanorods (AuNRs). These are functionalized or co-stabilized with different stoichiometric ratios of HS-(CH2)11-PEG-COOH and alkanethiols (Raman reporters), i.e.; HS-(CH2)11-NHCO-coumarin(C), HS-(CH2)11-triphenylimidazole (TPI), HS- (CH2)11-indole (HSI), HS-(CH2)11-hydroquinone (HQ) to form mixed monolayer protected clusters (MMPCs). The alkanethiols were chosen as Raman reporters to facilitate the selfassembled formation of monolayers on the metal surface, thus resulting in stable MMPCs. The optical properties and stability of MMPCs were obtained using ultraviolet-visible (UVvis) spectrophometry and a zeta sizer. Size and shape of the as-synthesized nanoparticles were obtained using transmission electron microscopy (TEM). The tendency of thiolcapped nanoparticles to form self-assembled ordered superlattices was observed. Their Raman activities were evaluated using Raman spectroscopy, with the enhancement factor (EF) being calculated from the intensities of symmetric stretch vibrations of C-H observed in the region of about 2900 to 3000 cm-1 in all SERS spectra. In all four different alkanethiols (Raman reporters), smaller size metal nanoparticles (14 nm for AuNPs and 16 nm AgNPs) showed higher EF compared to 30 and 40 nm metal nanoparticles. The EF was observed to increase proportionally with stoichiometric ratios of alkanethiols from 1% iv | P a g e to 50%. The prepared MMPCs with small sizes were used as a SERS probe for the detection of malaria and tuberculosis biomarkers.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2015.
Keywords: Raman spectroscopy.; Nanoparticles.; Malaria.; Tuberculosis.; Biochemical markers.